Impulsive Problems for Fractional Differential Equations with Nonlocal Boundary Value Conditions - Peiluan Li; Youlin Shang (Abstract and Applied Analysis)
We investigate the nonlocal boundary value problems of impulsive fractional differential equations. By Banach’s contraction mapping principle, Schaefer’s fixed point theorem, and the nonlinear alternative of Leray-Schauder type, some related new existence results are established via a new special hybrid singular type Gronwall inequality. At last, some examples are also given to illustrate the results.